DEF6 expression in ovarian carcinoma correlates with poor patient survival. Issue 1 (December 2016) - Liew, Phui-Ly; Fang, Chih-Yeu; Lee, Yu-Chieh; Lee, Yi-Chih; Chen, Chi-Long; Chu, Jan-Show
Abstract Background Increased expression of DEF6 is correlated with the malignant behavior of various cancers. Both DEF6 and p16 contribute to the regulation of cell cycle progression, and p53 plays important role in the cell cycle checkpoints. This study was designed to elucidate the prognostic significance of DEF6, p53 and p16 immunoexpressions in different histology subtypes of ovarian carcinoma. Methods Immunohistochemistry results of DEF6, p53 and p16 on ovarian carcinoma were compared with histology subtypes, clinical data, overall survival (OS) and disease-free survival (DFS) by Cox regression and Kaplan-Meier analysis. Results We studied 180 cases of ovarian carcinomas (75 high-grade serous, 41 clear cell, 36 mucinous and 28 endometrioid), including 109 FIGO stage I-II cases and 71 FIGO stage III-IV cases. Ovarian carcinomas positive for both DEF6 and p16 expression were associated with the worst OS (P = 0.027) and DFS (P = 0.023), whereas those negative for both DEF6 and p16 had the best OS and DFS. Aberrant p53 expression combined with positive DEF6 was associated with worst OS (P = 0.031) and DFS (P = 0.028). Kaplan-Meier analysis showed that significantly shorter survival rates were seen in patients with high expressions of DEF6 (P = 0.008) and p16 (P = 0.022). Patients with aberrant p53 expression in high-grade serous carcinoma (P = 0.012) and patients with high DEF6 expression in clear cell carcinoma (P = 0.001) were also associated with shorter overall survival. In univariate analysis, FIGO stage, DEF6 and p16 were associated with poor prognosis. DEF6 expression was the only independent prognostic factor correlated with shorted OS (HR 2.115;P = 0.025) and DFS (HR 2.248;P = 0.016) upon multivariate analysis. Conclusions DEF6 expression may serve as an independent prognostic factor, and interacted positively with p16 toward high tumor stage and shorter survival.